2021
DOI: 10.3389/fcimb.2021.619354
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parkinson’s Disease With Microbes and Microbiological Therapy

Abstract: Parkinson’s disease (PD) is the most common movement disorder in the world, affecting 1–2 per 1,000 of the population. The main pathological changes of PD are damage of dopaminergic neurons in substantia nigra of the central nervous system and formation of Lewy bodies. These pathological changes also occur in the intestinal tract and are strongly associated with changes in intestinal flora. By reviewing the research progress in PD and its association with intestinal flora in recent years, this review expounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 112 publications
2
23
0
Order By: Relevance
“…Furthermore, the fecal microbial community of PD has displayed a lower abundance of SCFA butyrate-producing bacteria that could be corrected by using prebiotics (Perez-Pardo et al 2017). This supports the potential clinical application of prebiotics in PD since their use has never been investigated in patients with PD (Chen et al 2021).…”
Section: Probiotics and Prebioticssupporting
confidence: 55%
“…Furthermore, the fecal microbial community of PD has displayed a lower abundance of SCFA butyrate-producing bacteria that could be corrected by using prebiotics (Perez-Pardo et al 2017). This supports the potential clinical application of prebiotics in PD since their use has never been investigated in patients with PD (Chen et al 2021).…”
Section: Probiotics and Prebioticssupporting
confidence: 55%
“…Advocating this view, it has been reported that the amount of butyrate correlate with the abundancies of bacteria of the genus Blautia and bacterial species such as Faecalibacterium prausnitzii and Roseburia faecis [64]. An enrichment of the genera Lactobacillus and Bifidobacterium in the fecal samples of PD patients has been reported in several studies [55,65]. The finding can be explained, at least partly, by the availability of these probiotics as commercial products.…”
Section: H 2 S Producing Colonic Bacteria and Pdmentioning
confidence: 92%
“…Apparent cross-feeding takes place between gDSV and genus Akkermansia. In studies on fecal samples, the relative overgrowth of the genus Akkermansia is a common finding in PD patients [55,56,65]. Akkermansia muciniphila, a bacterium residing abundantly in the mucus layer of the large intestine releases sulfate in mucin fermentation, thus offering sulfate to the mucosa-associated SRB [72,73].…”
Section: H 2 S Producing Colonic Bacteria and Pdmentioning
confidence: 99%
“…Other bacterial metabolites such as SCFAs, especially butyrate, serve an important role in maintaining intestinal integrity, and a lack of SCFAs can increase intestinal permeability. The decreased SCFA-producing bacteria in PD patients can lead to disruption of the intestinal mucosal barrier, and this serves as a prerequisite for entry of a-synuclein into the ENS to maintain excessive a-synuclein expression or even promote its misfolding (117). Therefore, the altered gut microbiota profiles and their bacterial metabolites can influence a-synuclein expression, misfolding, and transportation in the early stage of PD, which can be used as potential targets to antagonize a-synuclein pathology.…”
Section: A-synuclein Pathologymentioning
confidence: 99%